PENGARUH PERSENTASI LABA, BOOK TAX DIFFERENCE, INVESTMENT OPPORTUNITY SET DAN STRUKTUR MODAL TERHADAP EARNING RESPONSE COEFFICIENT DENGAN KONSEVATISME AKUNTANSI SEBAGAI MODERASI - Abbas, Dirvi Surya; Hakim, Mohamad Zulman; Utami, Salma Nur; Zakia, Siti; Yani, Sari Putri (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
This study is to determine the effect of Earnings Persistence, Book Tax Difference, Investment Opportunity Set and Capital Structure on Earnings Response Coefficient and Accounting Conservatism as a moderating variable. This study uses a quantitative approach, the research sample amounted to 13 companies. The sampling technique used is purposive sampling. The results of hypothesis research simultaneously show that the Earnings Persistence and Investment Opportunity Set variables have a significant effect on the Earnings Response Coefficient (ERC). Partial hypothesis research results Earnings Persistence and Investment Opportunity Set have a positive and significant effect on Earnings Response Coefficient. While Book Tax Difference and Capital Structure have no significant effect on Earnings Response Coefficient. Accounting Conservatism moderates Earnings Persistence and Investment Opportunity Set on Earnings Response Coefficient while Accounting Conservatism cannot moderate the effect of Book Tax Difference and Capital Structure on Earnings Response Coefficient